2005
DOI: 10.1113/expphysiol.2005.031112
|View full text |Cite
|
Sign up to set email alerts
|

Local transfer of prostaglandin E2 into the ovary and its retrograde transfer into the uterus in early pregnant sows

Abstract: This study was designed to establish (a) whether prostaglandin E 2 (PGE 2 ) can reach the ovary and oviduct by a local pathway and what is the contribution of lymphatic vessels to this transfer, and (b) whether PGE 2 can permeate from venous and lymphatic vessels of the mesometrium to arterial blood and be delivered to the uterine horn during maternal recognition of pregnancy in gilts. The reproductive tract was excised from gilts (n = 10) on day 14 after mating. The uterine horn was isolated with the ovary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…We suggest that PGE2 may also be produced by the endometrium from isolated part of the uterus and next be transported within the mesometrial blood and lymph vessels from one part of the uterus to another independently of the presence of embryos in the uterus. Our results confirmed the concept of local regulation of PGE2 secretion and its retrograde transfer into the uterus in pigs [32,48]. We demonstrated that isolation of one uterine horn both during days 12-14 of early pregnancy and the estrous cycle may enhance the mechanism of luteotrophic PGE2 production in the isolated part of the uterine horn.…”
supporting
confidence: 77%
“…We suggest that PGE2 may also be produced by the endometrium from isolated part of the uterus and next be transported within the mesometrial blood and lymph vessels from one part of the uterus to another independently of the presence of embryos in the uterus. Our results confirmed the concept of local regulation of PGE2 secretion and its retrograde transfer into the uterus in pigs [32,48]. We demonstrated that isolation of one uterine horn both during days 12-14 of early pregnancy and the estrous cycle may enhance the mechanism of luteotrophic PGE2 production in the isolated part of the uterine horn.…”
supporting
confidence: 77%
“…A similar effect occurs in lymphatic-arterial communications, as revealed in the ewe (Heap et al 1985(Heap et al , 1989 and sow (Krzymowski et al 1986, Stefańczyk--Krzymowska et al 2005, Chłopek et al 2008). Celia and Osol (2002) demonstrated that phenylephrine and acetylcholine infused into isolated rat uterine vein are able to alter the tone of adjacent uterine arteries in a concentration-dependent manner.…”
Section: Introductionsupporting
confidence: 53%
“…The local destination transfer of this PG to the ovary was, in early pregnancy, significantly reduced in comparison to the luteolysis period (Stefańczyk-Krzymowska et al 1990). However, transfer of PGE 2 to the ovary was intensified during the luteal phase of the estrous cycle and in early pregnancy and reduced in the luteolysis period (Stefańczyk-Krzymowska et al 2005, Chłopek et al 2008. This different distribution of PGs in reproductive organs may in turn change the function of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, an increased blood flow between uterus and ovary has been detected [29,30], as well as a segregation of progesterone by the corpus luteum to maintain the lining of the endometrium in early pregnancy. Other studies in pigs [31] have also shown that ovarian hormones influence retrograde transfer of prostaglandin E 2 secreted by the conceptus. Despite this previous evidence, the majority of expression studies in porcine reproductive tissues have been carried out mainly in preimplantation uterus [2].…”
Section: Discussionmentioning
confidence: 92%